2016
DOI: 10.1371/journal.pone.0147615
|View full text |Cite
|
Sign up to set email alerts
|

IL-10 Accelerates Re-Endothelialization and Inhibits Post-Injury Intimal Hyperplasia following Carotid Artery Denudation

Abstract: The role of inflammation on atherosclerosis and restenosis is well established. Restenosis is thought to be a complex response to injury, which includes early thrombus formation, acute inflammation and neo-intimal growth. Inflammatory cells are likely contributors in the host response to vascular injury, via cytokines and chemokines secretion, including TNF-alpha (TNF). We have previously shown that IL-10 inhibits TNF and other inflammatory mediators produced in response to cardiovascular injuries. The specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 34 publications
(54 reference statements)
3
13
0
Order By: Relevance
“…Earlier reports have identified increased IL-10 levels following injury of rat sciatic nerve, and a beneficial role of IL-10 has been implicated in tissues such as cardiac muscle, carotid endothelia, and lung epithelia (20)(21)(22). We found that epithelial IL-10Rα mediates the IL-10-driven increase in wound healing.…”
Section: Discussionsupporting
confidence: 56%
“…Earlier reports have identified increased IL-10 levels following injury of rat sciatic nerve, and a beneficial role of IL-10 has been implicated in tissues such as cardiac muscle, carotid endothelia, and lung epithelia (20)(21)(22). We found that epithelial IL-10Rα mediates the IL-10-driven increase in wound healing.…”
Section: Discussionsupporting
confidence: 56%
“…Several studies have shown an increase on neointima proliferation after angioplasty due to an inhibited endothelial recovery 28 . Since endothelial repair is an important component of the adaptive response of the vessel to injury, we examined this process in our model by immunofluorescent staining for CD31, a specific marker of endothelial cells.…”
Section: Resultsmentioning
confidence: 99%
“…We previously reported that pMSCs produce many molecules with survival, pro-proliferative, and migratory activities, such as IL-6 [ 28 ], IL-8 [ 29 , 30 ], IL-10 [ 31 ], IL-11 [ 32 ], and PDGF-Rβ [ 33 ]. These molecules potentially mediate the pMSC protective effects on endothelial cells treated with glucose.…”
Section: Discussionmentioning
confidence: 99%